2017
DOI: 10.1248/bpb.b17-00557
|View full text |Cite
|
Sign up to set email alerts
|

Dibutyl Phthalate Rather than Monobutyl Phthalate Facilitates Contact Hypersensitivity to Fluorescein Isothiocyanate in a Mouse Model

Abstract: Dibutyl phthalate (DBP) is a plasticizer used for many consumer products including cosmetics. Potential health concerns regarding DBP include reproductive and developmental toxicity, endocrine disruption and neurotoxicity. DBP is a high priority chemical as to reduction of exposure of children to it. Through reproductive toxicity studies, monobutyl phthalate (MBP) has been proposed to be the active metabolite derived from DBP. We previously demonstrated that DBP activates transient receptor potential ankyrin 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Jahreis et al (2018) found such effects even in the second (F2) generation after exposure to BBP of the parent mice. Enhanced antibody responses to thyroid globulin by exposure to DBP was observed by Wu et al (2017), and enhanced skin sensitisation by DBP, DINP, DIDP was described by Kang et al (2016Kang et al ( , 2017; Shen et al (2017) and Kurohane et al (2017).…”
Section: Updated Literature On Immunotoxic Effects Of Phthalatesmentioning
confidence: 96%
“…Jahreis et al (2018) found such effects even in the second (F2) generation after exposure to BBP of the parent mice. Enhanced antibody responses to thyroid globulin by exposure to DBP was observed by Wu et al (2017), and enhanced skin sensitisation by DBP, DINP, DIDP was described by Kang et al (2016Kang et al ( , 2017; Shen et al (2017) and Kurohane et al (2017).…”
Section: Updated Literature On Immunotoxic Effects Of Phthalatesmentioning
confidence: 96%
“…Cells Chinese hamster ovary (CHO) cells expressing human TRPA1 (TRPA1-CHO) were used as described previously. 10,11,14,15) Animals Specific pathogen-free female BALB/c mice were purchased from Japan SLC Inc. (Shizuoka, Japan) at 7 weeks of age and held for 1 week before use for acclimatization. They were housed at 22 to 24°C with 50 to 60% humidity under artificial lighting conditions with a 12-h light/ dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…TRPA1 Activation in Vitro TRPA1-CHO cells were labeled with a calcium ion-sensitive fluorescent probe, Fluo 4-AM After automatic addition of a test sample (prepared in DMSO) in the presence or absence of a TRPA1 antagonist, HC-030031, the intracellular Ca 2+ level was measured over time with a fluorometric imaging plate reader, FLEXstation II (Molecular Devices, Sunnyvale, CA, U.S.A.) at 37°C as described previously. [12][13][14] The maximal Ca 2+ level was determined using 5 μM ionomycin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations